KOMPLEMENTARIANISME - Edi Prasetyo Nugroho (Faculty of Economics and Business, Universitas Gadjah Mada, 2000)
The general templates of business and economic activities up to the beginning of this millenium are still dominated by competition models. To exist in such dynamic business environment, many business players still assuming that the most appropriate perspective to be used in anticipating the dynamics is by winning the competition. All efforts are directed to beat the competitors that based on a classical reason: satisfying the customers!! But, at the same time, we also observe that high competition environment is not only drive to the ideal results (customer satisfaction) but also potentially directing people to dehumanize other people. From those situation, I try to propose a concept namely Complementarianism to balance the people orientation in human transactional setting. I do believe that the appropriate premises to explain about the future issues to exist in business are not only maintaining Sustainable Competitive Advantages but also creatively and innovatively promoting what we call as Sustainable Complementary Advantages.